2022
DOI: 10.1007/s10433-022-00703-4
|View full text |Cite|
|
Sign up to set email alerts
|

Revisiting the Nordic long-term care model for older people—still equal?

Abstract: With the extensive long-term care services for older people, the Nordic countries have been labelled ‘caring states’ as reported (Leira, Welfare state and working mothers: the Scandinavian experience, Cambridge University Press, Cambridge, 1992). The emphasis on services and not cash benefits ensures the Nordics a central place in the public service model (Anttonen and Sipilä, J Eur Soc Policy 6:87–100, 1996). The main feature of this ideal model is public social care services, such as home care and residentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 41 publications
(48 reference statements)
1
46
1
1
Order By: Relevance
“…When the overall coverage reduces, and the eligibility thresholds are relatively strict, older adults must have quite severe health problems to qualify for formal care. Consequently, the adult children of parents with less-severe health problems but who still need care will be affected (Rostgaard et al 2022 ). However, this study shows that even when accounting for formal care received by parents, care received from children still vary depending on their gender and social class combined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the overall coverage reduces, and the eligibility thresholds are relatively strict, older adults must have quite severe health problems to qualify for formal care. Consequently, the adult children of parents with less-severe health problems but who still need care will be affected (Rostgaard et al 2022 ). However, this study shows that even when accounting for formal care received by parents, care received from children still vary depending on their gender and social class combined.…”
Section: Discussionmentioning
confidence: 99%
“…publicly funded care for older adults should be available to all as needed, regardless of an individual’s financial or family resources (Sipilä 2019 ). However, care provided by the state has undergone a process of deinstitutionalisation and marketisation, having various implications for the lives of older adults and their families (Rostgaard et al 2022 ). Older adults needing care appear to arrange their care provision depending on their socioeconomic status, especially if they do not qualify for formal services.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, local governments with a social democratic orientation may be more inclined to allocate excessive public resources to the LTC system than those with a liberal capitalist orientation [ 9 ]. Recent research has also found that local governments’ differential prioritization of LTC systems in overall social security policy and differential emphasis on institutional and family services have contributed to significant differences in the geographic distribution of existing LTC systems [ 10 , 11 ]. These differences can hardly be explained by the changes in the population size and needs of the elderly, but the results all lead to the inequality and unfairness of LTC.…”
Section: Introductionmentioning
confidence: 99%
“…Due to different systems of LTC, given a certain level of care needs, the use of services varies across countries [ 10 , 11 ]. In the Nordic countries LTC is largely publicly financed with the goal of an equitable allocation of care on the basis of universalism [ 12 ], e.g., access to LTC is needs-tested rather than means-tested. Although aging-in-place, e.g., to assist older people in their own homes, is promoted in all Nordic countries [ 13 , 14 ], the use of LTC depends on the country-specific welfare system.…”
Section: Introductionmentioning
confidence: 99%
“…Although aging-in-place, e.g., to assist older people in their own homes, is promoted in all Nordic countries [ 13 , 14 ], the use of LTC depends on the country-specific welfare system. Although several European countries impose legal obligation to family members to provide care support to older adults [ 15 ], in the Nordic countries, there is no formal obligation nor strong norms for the family to care for older parents [ 12 , 16 ].…”
Section: Introductionmentioning
confidence: 99%